2017
DOI: 10.1094/pdis-10-16-1543-re
|View full text |Cite
|
Sign up to set email alerts
|

Viral Diversity in Autochthonous Croatian Grapevine Cultivars

Abstract: TitleViral diversity in autochthonous croatian grapevine cultivars Permalink https://escholarship.org/uc/item/86j0p6dv JournalPlant Disease, 101 (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…GRGV was detected in many of our samples but its presence could only be validated in seven libraries (Table 1 ,Figure 2B ). GRGV has been identified in different parts of Europe (Sabanadzovic et al, 2000 ; Beuve et al, 2015 ; Cretazzo et al, 2017 ; Voncina et al, 2017 ) and also in California (El Beaino et al, 2001 ) and in Brazil (Fajardo et al, 2017 ). We detected GRGV in different regions of the country; the sequenced strains have 87–95% identity with the Reference strain (NC_030693) and clustered separately (Supplementary Figure 2H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GRGV was detected in many of our samples but its presence could only be validated in seven libraries (Table 1 ,Figure 2B ). GRGV has been identified in different parts of Europe (Sabanadzovic et al, 2000 ; Beuve et al, 2015 ; Cretazzo et al, 2017 ; Voncina et al, 2017 ) and also in California (El Beaino et al, 2001 ) and in Brazil (Fajardo et al, 2017 ). We detected GRGV in different regions of the country; the sequenced strains have 87–95% identity with the Reference strain (NC_030693) and clustered separately (Supplementary Figure 2H ).…”
Section: Resultsmentioning
confidence: 99%
“…In 10_EH the low amount of loaded RNA, whereas in 11_SZHU low amount of GPGV could be the reason why we couldn't get a signal. Since its first description (Giampetruzzi et al, 2012 ) GPGV has been reported from all over the world, including Slovakia (Glasa et al, 2014 ), Slovenia (Plesko et al, 2014 ), Croatia (Voncina et al, 2017 ), Serbia, Romania, and Ukraine (Bertazzon et al, 2016 ), i.e., almost all of Hungary's neighboring countries. According to their CP sequences our isolates showed slight variation, but grouped distantly and together with isolates of different geographical origins (Supplementary Figure 2M ), which supports the possibility that GPGV spread from Eastern Europe to Italy (Bertazzon et al, 2016 ; Malagnini et al, 2016 ), and from Europe to other parts of the world (Wu and Habili, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, the most damaging virus strains are listed in the classification of the European and Mediterranean Plant Protection Organization (EPPO 2019). The most widespread are Grapevine leafroll-associated virus 1, 2 and 3 (GLRaV-1, GLRaV-2 and GLRaV-3), Arabis mosaic virus (ArMV), Grapevine fleck virus (GFkV) and Grapevine fanleaf virus (GFLV) (Vončina et al 2017, Xiao et al 2018. According to the propositions of EPPO, certified virus-free vines should be free of these 5 viruses: ArMV, GFLV, GL-RaV-1, GLRaV-3 and GFkV (only rootstocks).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that viruses GFLV, GLRaV-1, -3 and GFkV present in donor plants were successfully eliminated by SE. This is also one of only a few reports that includes detection of viruses in Croatian cultivars by RT-PCR (Vončina et al 2017), a method that has a higher sensitivity than the routinely used serological ELISA (Gambino and Gribaudo 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Already-known viruses-GLRaV-3, GRSPaV, GVA, and GVE-were detected. NGS can be further used to study genetic biodiversity and the spread of viruses and viroids [78,128,[132][133][134][135][136][137][138].…”
Section: Next-generation Sequencing: a New Approach To Viral Diagnosismentioning
confidence: 99%